Assessment of Sustainable Pedagogical Orientation and Practices of Secondary School Teachers in Osun State, Nigeria - Yusuf Olayinka Shogbesan; Adebukola Nusirat Tiamiyu; Peter Sanjo Adewale,; Chansa Thelma Chanda; Abayomi Israel Olaofe (Educational Considerations, 2025)
The study investigates secondary school teachers in Osun State, Nigeria, regarding their sustainable pedagogical orientations. The study also examines primary sustainable pedagogical methods used by teachers while also analyzing their difficulties with sustainable teaching implementation. It also examines if gender creates any substantial difference regarding sustainable pedagogical orientations within the secondary school teaching workforce. A descriptive survey research design led to the selection of n=180 senior secondary school teachers from 30 schools located in three Local Government Areas (Olorunda, Oriade, and Ife Central) through a multi-stage sampling procedure. A self-constructed questionnaire was used to collect data from the respondents with 4-point Likert Scale, validated by a team of test experts, and test-retest procedure was used to conduct the reliability. Both descriptive and inferential statistical methods were used to analysis the data. The findings reveal that educators understand sustainability effectively but fail to put these ideas into practice because training resources are inadequate and institutions provide weak support along with insufficient funding. The main obstacles teachers face in their planning processes stem from limited time for preparation and restricted access to modern educational resources as well as a poor match between sustainability units and standardized teaching materials. The research established a major disparity between male and female teachers regarding sustainability teaching methods which indicate gender might impact how sustainability functions in education. The research recommends that schools need better training systems together with additional funding and modernized teaching structure to help teachers embed sustainability education throughout their classroom practices.
Keywords: Curriculum Frameworks; Sustainable Pedagogical Practices; Secondary School Teachers; Sustainable Development Goals (SDGs); Professional Development